-16x-96=4(x-64)

Simple and best practice solution for -16x-96=4(x-64) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16x-96=4(x-64) equation:


Simplifying
-16x + -96 = 4(x + -64)

Reorder the terms:
-96 + -16x = 4(x + -64)

Reorder the terms:
-96 + -16x = 4(-64 + x)
-96 + -16x = (-64 * 4 + x * 4)
-96 + -16x = (-256 + 4x)

Solving
-96 + -16x = -256 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-96 + -16x + -4x = -256 + 4x + -4x

Combine like terms: -16x + -4x = -20x
-96 + -20x = -256 + 4x + -4x

Combine like terms: 4x + -4x = 0
-96 + -20x = -256 + 0
-96 + -20x = -256

Add '96' to each side of the equation.
-96 + 96 + -20x = -256 + 96

Combine like terms: -96 + 96 = 0
0 + -20x = -256 + 96
-20x = -256 + 96

Combine like terms: -256 + 96 = -160
-20x = -160

Divide each side by '-20'.
x = 8

Simplifying
x = 8

See similar equations:

| -4/5x+7=-151/5-7x | | 2-11b=8b+15 | | 12xc=1.08 | | (3v-9)/10=(v+3)/7 | | 7x+2y=15fory | | 8x=57-3y | | -17=2n+13-18n | | (-8)-(-39)= | | 3x+7=x+7 | | 254-5d=d | | 11xk=9 | | 8x+40=-4x-32 | | 5j-10=20 | | d+c/b=a | | 3/6f+1/2=6(1/16f-3) | | 4=-16x | | 0.5(2x-6)=0.5x+1 | | 3s-8=13 | | 196r^2-100= | | 3/8=(7n-10)/(n+2) | | 8x+5=-4x-32 | | -24-1/8p=3/p | | 6x+4=-7x+121 | | 103/4x22/3 | | 2x(-3+4)=8 | | x*x+2=36 | | 5y=-7-2x | | 11+8q=3q-194 | | -3(x-1)+2x=3x-7 | | 21+1/8+2t | | 7/(a-9)=-2/(a+9) | | 4x+4=-2x+52 |

Equations solver categories